NMR Screen Reveals the Diverse Structural Landscape of a G-Quadruplex Library - Sgallová, Ráchel; Volek, Martin; Kurfürst, Jaroslav; Srb, Pavel; Veverka, Václav; Curtis, Edward A (Chemistry (Weinheim an der Bergstrasse, Germany), 2024)
G-quadruplexes are noncanonical nucleic acid structures formed by stacked guanosine tetrads. Despite their functional and structural diversity, a single consensus model is typically used to describe sequences with the potential to form G-quadruplex structures. We are interested in developing more specific sequence models for G-quadruplexes. In previous work, we functionally characterized each sequence in a 496-member library of variants of a monomeric reference G-quadruplex for the ability to bind GTP, promote a model peroxidase reaction, generate intrinsic fluorescence, and to form multimers. Here we used NMR to obtain a broad overview of the structural features of this library. After determining the 1H NMR spectrum of each of these 496 sequences, spectra were sorted into multiple classes, most of which could be rationalized based on mutational patterns in the primary sequence. A more detailed screen using representative sequences provided additional information about spectral classes, and confirmed that the classes determined based on analysis of 1H NMR spectra are correlated with functional categories identified in previous studies. These results provide new insights into the surprising structural diversity of this library. They also show how NMR can be used to identify classes of sequences with distinct mutational signatures and functions.
Keywords: G-quadruplex; Multimeric structures; mutace; Guanosine Triphosphate; G-kvadruplexy; Mutation; G-Quadruplexes; NMR; guanosintrifosfát; DNA; Magnetic Resonance Spectroscopy; magnetická rezonanční spektroskopie